Synthesis and Characterization of Iron Oxide Nanoparticles and Applications in the Removal of Heavy Metals from Industrial Wastewater - Zuolian Cheng; Annie Lai Kuan Tan; Yong Tao; Dan Shan; Kok Eng Ting; Xi Jiang Yin (International Journal of Photoenergy)
This study investigated the applicability of maghemite (γ-Fe2O3) nanoparticles for the selective removal of toxic heavy metals from electroplating wastewater. The maghemite nanoparticles of 60 nm were synthesized using a coprecipitation method and characterized by X-ray diffraction (XRD) and scanning electron microscopy (SEM) equipped with energy dispersive X-ray spectroscopy (EDX). Batch experiments were carried out for the removal of Pb2+ ions from aqueous solutions by maghemite nanoparticles. The effects of contact time, initial concentration of Pb2+ ions, solution pH, and salinity on the amount of Pb2+ removed were investigated. The adsorption process was found to be highly pH dependent, which made the nanoparticles selectively adsorb this metal from wastewater. The adsorption of Pb2+ reached equilibrium rapidly within 15 min and the adsorption data were well fitted with the Langmuir isotherm.